2011
DOI: 10.1016/j.electacta.2011.02.114
|View full text |Cite
|
Sign up to set email alerts
|

TiO2-graphene nanocomposite for electrochemical sensing of adenine and guanine

Abstract: a b s t r a c tTiO 2 -graphene nanocomposite was prepared by hydrolysis of titanium isopropoxide in colloidal suspension of graphene oxide and in situ hydrothermal treatment. It provides an efficient and facile approach to yield nanocomposite with TiO 2 nanoparticles uniformly embedded on graphene substrate. The electrochemical behavior of adenine and guanine at the TiO 2 -graphene nanocomposite modified glassy carbon electrode was investigated. The results show that the incorporation of TiO 2 nanoparticles wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(90 citation statements)
references
References 47 publications
5
82
0
Order By: Relevance
“…This remarkable electrochemical sensing performance was attributed to good catalytic property and large active surface area of the PGA film which provided an efficient microenvironment for electrochemical reaction of EP and UA. 34 …”
Section: Sensitive Determination Of Ep and Uamentioning
confidence: 99%
“…This remarkable electrochemical sensing performance was attributed to good catalytic property and large active surface area of the PGA film which provided an efficient microenvironment for electrochemical reaction of EP and UA. 34 …”
Section: Sensitive Determination Of Ep and Uamentioning
confidence: 99%
“…148,149 Fan et al showed that the electrocatalytic activity of adenine and guanine increased in glassy carbon electrodes modified with TiO 2 -graphene composites. 150 Zeolite modifications have also been widely studied 151,152 . Zeolites are microporous aluminosilicate minerals characterized by their ability to be hydrated and dehydrated reversibly.…”
Section: Modified Electrodesmentioning
confidence: 99%
“…For example, pulse laser deposition was applied to deposit V 2 O 5 film on the graphene paper surface to yield flexible energy storage devices [81]. NiO [82], TiO 2 [83][84][85], indium-gallium-zinc oxide [86] and PtNPs/MnO 2 nanowires [61] were all successfully deposited onto graphene paper surfaces for specific functionalization. In addition, non-metallic nanostructures such as those carbon-containing building blocks (e.g.…”
Section: Metallic Compound Nanostructuresmentioning
confidence: 99%